Relationship between family background and self-efficacy in adolescent table tennis players: a moderated mediation model - He, Ke; Li, Weiming; Li, Zihao (Frontiers in Psychology, 2023)
A moderated mediation model was constructed in this study to clarify the relationship between family background and self-efficacy of adolescent table tennis players, focusing on the mediating effect of technical learning engagement in the relationship as well as the moderating role of factors such as gender and training years. 189 adolescent table tennis players (age: 13.69±1.28 years) were investigated as subjects using a questionnaire method. The results revealed that (1) family background, technical learning engagement, and self-efficacy were significantly and positively correlated (p<0.01), with girls' technical learning engagement (M female=5.81, M male=5.19, p<0.01) and self-efficacy (M female=3.34, M male=2.66, p<0.01) significantly higher than boys'; (2) technical learning engagement partially mediated the effect of family background on self-efficacy (ab=0.10, boot SE=0.02,95% CI=[0.07, 0.14]); (3) the first half of technical learning engagement's mediating role was moderated by gender (B=0.05, p<0.01), with a more significant influence of family background on boys' (B=0.24, p<0.001, 95% CI=[0.22, 0.26]) technical learning engagement than girls' (B=0.19, p<0.001, 95% CI=[0.17, 0.21]); (4) the second half of technical learning engagement's mediating role was moderated by training years (B=-0.21, p <0.001), with a more significant influence of technical learning engagement on the self-efficacy of adolescents with fewer training years (B=0.54, p<0.001, 95% CI=[0.39, 0.68]). The positive effect of technical learning engagement on self-efficacy gradually diminished with increasing training years, and the moderating effect of training years disappeared when the training years reached 8.94 years.